WORLD VIEW PENDIDIKAN ISLAM TENTANG PEMBENTUKAN KARAKTER PESERTA DIDIK YANG HOLISTIK DAN INTEGRATIF - Samsul Bahri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
This paper discusses the world view of Islamic education on the formation of the character of learners are holistic and integrative. The method used is descriptive analysis by using historical approach. This study proves that the world view of Islamic education in character education has become the vision and mission of Islamic education, it is seen in the goal of Islamic education, the responsibility of educators. This study also concludes the prophetic mission of Islamic education is to develop character education of students or morality and educate individuals to believe in God and implement their Shari'ah. It's just that this mission has not been achieved because it stumbles with a mall-educational practice. Therefore, teachers are willing to innovate and creativity to characterize character education strategies in a balanced way through implementation in learning through exemplary.